Conditional deletion of KCC2 impairs synaptic plasticity and both spatial and nonspatial memory - Kreis, Anna; Issa, Farah; Yerna, Xavier; Jabbour, Caren; Schakman, Olivier; de Clippele, Marie; Tajeddine, Nicolas; Pierrot, Nathalie; Octave, Jean-Noël; Gualdani, Roberta; Gailly, Philippe (Frontiers in Molecular Neuroscience, 2023)
The postsynaptic inhibition through GABAA receptors (GABAAR) relies on two mechanisms, a shunting effect due to an increase in the postsynaptic membrane conductance and, in mature neurons, a hyperpolarization effect due to an entry of chloride into postsynaptic neurons. The second effect requires the action of the K+–Cl− cotransporter KCC2 which extrudes Cl− from the cell and maintains its cytosolic concentration very low. Neuronal chloride equilibrium seems to be dysregulated in several neurological and psychiatric conditions such as epilepsy, anxiety, schizophrenia, Down syndrome, or Alzheimer’s disease. In the present study, we used the KCC2 Cre-lox knockdown system to investigate the role of KCC2 in synaptic plasticity and memory formation in adult mice. Tamoxifen-induced conditional deletion of KCC2 in glutamatergic neurons of the forebrain was performed at 3  months of age and resulted in spatial and nonspatial learning impairment. On brain slices, the stimulation of Schaffer collaterals by a theta burst induced long-term potentiation (LTP). The lack of KCC2 did not affect potentiation of field excitatory postsynaptic potentials (fEPSP) measured in the stratum radiatum (dendrites) but increased population spike (PS) amplitudes measured in the CA1 somatic layer, suggesting a reinforcement of the EPSP-PS potentiation, i.e., an increased ability of EPSPs to generate action potentials. At the cellular level, KCC2 deletion induced a positive shift in the reversal potential of GABAAR-driven Cl− currents (EGABA), suggesting an intracellular accumulation of chloride subsequent to the downregulation of KCC2. After treatment with bumetanide, an antagonist of the Na+-K+-Cl− cotransporter NKCC1, spatial memory impairment, chloride accumulation, and EPSP-PS potentiation were rescued in mice lacking KCC2. The presented results emphasize the importance of chloride equilibrium and GABA-inhibiting ability in synaptic plasticity and memory formation.